The Effect of Ownership Structure on Cash Conversion Cycle in Listed Firms on Tehran Stock Exchange - Javadi, Elaheh; Nikoumaram, Hashem (International Journal of Economics and Financial Issues, 2017)
This study aims to investigate the effect of ownership structure in terms of ownership type and ownership concentrate on cash conversion cycle in 115 listed firms on Tehran Stock Exchange between 2008 and 2014. The theoretical basis and the data used in this study were obtained through library research. Also, the hypotheses formulated in the present research were tested using correlation analysis based on multivariate regression analysis. The results obtained by testing the hypotheses show that there is a significant and negative correlation between institutional ownership and cash conversion cycle and a significant and positive correlation between firm ownership and cash conversion cycle. The results of the study also indicate that there is not a significant correlation between major shareholder ownership and cash conversion cycle. Keywords: Cash Conversion Cycle, Ownership Structure, Institutional Ownership, Cash JEL Classifications: C32; O13; O47